Pengembangan Permainan Eurythmics Terhadap Kreativitas Musik Siswa Kelas V di Sekolah Dasar - Sabila Ribathil Wuddat; Respati , Resa Respati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop the Eurythmics game as a learning medium to enhance the musical creativity of fifth-grade elementary school students. The background of this study is the limited music learning that provides space for students to express themselves actively and creatively. The music learning process in elementary schools is generally still focused on theory, so it does not support the development of students' musical creativity. This study uses an Educational Design Research (EDR) approach that includes the stages of problem analysis, design, development, trial, and reflection. The research subjects were fifth-grade elementary school students. Data collection techniques were carried out through observation, interviews, and documentation to observe the learning process and the development of students' musical creativity. The results of the study indicate that the developed Eurythmics game can create a more active, enjoyable, and interactive learning. Students become more daring in exploring rhythm, movement, and sound in musical activities. In addition, there is an increase in students' musical creativity as seen from their improvisational skills, rhythmic variations, and better musical expression. Thus, the Eurythmics game is effective for use as a learning medium to enhance the musical creativity of elementary school students. This developed product is also suitable for use as an alternative method of learning music arts that is innovative and appropriate to the learning needs in elementary schools.